Descriptions of eight new species of Grouvellinus from China (Coleoptera, Elmidae) - Bian, Dongju; Zhang, Yi (Zootaxa, 2023)
Eight new species are described from Yunnan, China (Grouvellinus elongatus sp. nov., G. ligulaceus sp. nov., G. lubricus sp. nov., G. macilentus sp. nov., G. nujiangensis sp. nov., G. pengi sp. nov., G. spiculatus sp. nov., G. spnaericus sp. nov.). Habitus, male genitalia photographs, and diagnosis are provided.